2019 Novel Human Coronavirus Sars-Cov-2 And Covid-19: A Brief Review: Life Sciences-Bioinformatics for health care - Satyabrata Sahoo; Ria Rakshit (International Journal of Life Science and Pharma Research, 2022)
The emergence of the 2019 novel coronavirus SARS-CoV-2, causing a highly contagious disease COVID-19 poses a tremendous global public health concern. As the disease is quickly developing into a worldwide pandemic, a careful analysis of its origin, evolution, transmission, and cellular mechanism is urgently needed to combat the deadly virus. Successful isolation of the 2019-nCoV has promoted some bioinformatic studies to understand the viral origin and the feature of its infectivity. However, at this stage, much remains unclear about the origin of the novel virus and to be investigated to develop ways to control its spread. The mechanisms associated with the infectiousness of SARS-CoV-2 are not entirely understood. The current knowledge in 2019-nCoV pathogenicity and transmissibility along with several commonly known emerging viruses and information is very much important for better control of the disease. So far, the treatment is only supportive. Any antiviral agent is yet to emerge. The scientific community raced to understand the pathogenesis of the disease for developing treatment options. Extensive research is going on to understand the host response to the pandemic virus to develop the disease therapeutic. To fill the knowledge gap about the human immune response to SARS-CoV- 2 infections that may help in designing the appropriate immune intervention for treatment, diagnosis, and prophylactic/therapeutic vaccines against COVID-19, we present hereby a brief review on the genomic organization, origin, and evolution, transmission and pathogenesis of the novel virus, and clinical spectrum and possible preventive measures against COVID-19 which may be used for future references.